2016
DOI: 10.1016/j.exer.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Variations in active outflow along the trabecular outflow pathway

Abstract: Previous tracer studies have shown segmental outflow in the trabecular meshwork (TM) and along the inner wall (IW) of Schlemm’s canal (SC). Whether segmental outflow is conserved distal to SC has not yet been investigated. This study aims to investigate whether the segmented pattern of outflow is conserved in distal outflow pathways by using a newly developed global imaging method and to evaluate variations of active outflow in three distinct regions along trabecular outflow pathway. Six normal whole globe hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 23 publications
7
90
1
1
Order By: Relevance
“…The outflow of aqueous humor has its segmental patterns around the SC circumference, and the majority of AH outflow is likely through the inferior collector channels. 25,26 Overall, the distal flow structures (e.g., collector channels and episcleral veins) may be have more importance than previously believed. Our results showed that the SC parameters of inferior quadrant were smaller than the other three quadrants.…”
Section: Discussionmentioning
confidence: 65%
“…The outflow of aqueous humor has its segmental patterns around the SC circumference, and the majority of AH outflow is likely through the inferior collector channels. 25,26 Overall, the distal flow structures (e.g., collector channels and episcleral veins) may be have more importance than previously believed. Our results showed that the SC parameters of inferior quadrant were smaller than the other three quadrants.…”
Section: Discussionmentioning
confidence: 65%
“…An unequal distribution of ESVs in different regions has been shown. The nasal region has been found to contain significantly more ESVs than the temporal region [17]. There is some debate about whether or not the CC ostia are concentrated in the lower nasal region.…”
Section: Discussionmentioning
confidence: 99%
“…There is some debate about whether or not the CC ostia are concentrated in the lower nasal region. According to Cha, CCs are concentrated in the lower nasal region [17]. However, Hann [18] reported that CCs are uniformly distributed along the outer wall of SCs.…”
Section: Discussionmentioning
confidence: 99%
“…Focal changes of conventional aqueous humor outflow are difficult to examine, 8,28 yet are crucial to better understand how elements downstream of the TM may influence outflow. There is ample new clinical evidence [29][30][31][32][33] that very significant outflow resistance exists downstream of the trabecular meshwork as trabecular ablation rarely achieves the theoretically lowest intraocular pressure, which would be equal to that of episcleral venous pressure according to the Goldmann equation.…”
Section: Discussionmentioning
confidence: 99%